Senescence controls prostatic neoplasia driven by Pten loss. (2nd January 2019) - Parisotto, Maxime; Grelet, Elise; El Bizri, Rana; Metzger, Daniel
ABSTRACT: We report that Pten (phosphatase and tensin homologue) ablation in prostatic epithelial cells of adult mice promotes cell proliferation to generate prostatic intraepithelial neoplasia. Moreover, our results demonstrate that proliferating Pten-deficient cells undergo replication stress and exhibit a DNA damage response, leading to cell senescence, as seen in oncogene-induced senescence.